2013
DOI: 10.1515/lp-2013-0013
|View full text |Cite
|
Sign up to set email alerts
|

Gradient clash, faithfulness, and sonority sequencing effects in Russian compound stress

Abstract: Russian normally does not have secondary stress, but it is variably realized in compounds. We examined the factors that contribute to secondary stress realization in a rating study, where listeners were asked to rate compounds pronounced without secondary stress and with secondary stress in various locations. We refine some generalizations from impressionistic descriptions: in compounds whose left-hand stems have mobile lexical stress, acceptability of secondary stress decreases with token frequency of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
0
5
2
Order By: Relevance
“…The present findings do not align with the results of previous empirical research investigating the division of the Russian lexicon into different stem types, conducted by Gouskova & Roon (2013) and Mołczanow et al . (2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The present findings do not align with the results of previous empirical research investigating the division of the Russian lexicon into different stem types, conducted by Gouskova & Roon (2013) and Mołczanow et al . (2013).…”
Section: Discussioncontrasting
confidence: 99%
“…The present findings do not align with the results of previous empirical research investigating the division of the Russian lexicon into different stem types, conducted by Gouskova & Roon (2013) and Mołczanow et al (2013). Gouskova & Roon ran a rating study of secondary stress in compounds, which revealed a difference between stems with fixed stress and those with non-fixed stress.…”
Section: Accented and Unaccented Stem Typescontrasting
confidence: 99%
“…It is very common for phonotactic constraints to apply differently to words with one root versus compounds-words with more than one root. Thus, in Russian (Gouskova and Roon 2013) and Polish (Newlin-Łukowicz 2012), as well as many other languages, there is one stress per phonological word regardless of length unless that word is a compound, in which case a weaker, secondary stress appears on the left-hand stem of the compound.…”
Section: Domain-sensitive Phonotactic Generalizationsmentioning
confidence: 99%
“…The effects are found independently in lemmata of two, three, and four syllables and are argued not to be confounded by vowel qualities, yers, or palatals. Beyond onset complexity, Gouskova and Roon (2013) find that the quality of segments in complex onsets affects the distribution of secondary stress in Russian compounds (e.g. falling-sonority ld is more stress-attracting than rising-sonority zl; the extent to which these differences correlate with duration or p-center differences remains to be explored).…”
Section: 2mentioning
confidence: 99%